The Effect Of Work-Life Balance, Job Burnout, Organizational Commitment on Turnover Intention at XYZ Hospital in Bekasi - Manurung, Rahel Novianti; Bernarto, Innocentius (MEC-J (Management and Economics Journal), 2024)
Providing the best service in hospital is very important due to very competitive competition. Nurses are the main providers of services especially in private hospitals. The aim of this study is to assess the association between work-life balance, job burnout, and organizational commitment on turnover intention at XYZ Hospital in Bekasi. Data collection using online questionnaires from 120 nurses was done for this quantitative investigation. Work-life balance, job burnout, and organizational commitment were the independent factors, while turnover intention which was projected at the conclusion of the modelling process was the dependent variable. Partial least squares-structural equation modelling (PLS-SEM) was utilized in data analysis. The findings showed that work-life balance has a negative effect on job burnout, work-life balance has a positive effect on organizational commitment, job burnout has a positive effect on turnover intention, organizational commitment has a negative effect on job burnout, and work-life balance has a negative effect on turnover intention. Based on the results of this study, it can be concluded that job burnout has a very strong influence on turnover intention